The irony of rigor: 'no-excuses' charter schools at the intersections of race and disability. Issue 3 (16th March 2019) - Waitoller, Federico R.; Nguyen, Nicole; Super, Gia
Abstract: Across the United States, the 'no-excuses' charter school movement featuring strict discipline policies and rigorous academic standards has gained popularity among schools serving poor and working-class students of color. In this article, we examine how Black and Latinx parents of students with disabilities 1 negotiated and experienced these charter school practices of rigor, which disciplined, managed, and regulated students' social differences. Drawing from a yearlong qualitative research study, we examine interviews with Black and Latinx parents who experienced conflict with charter schools and the school lawyers, along with school artifacts we gathered such as parent handbooks and website information. We found parents experienced what we refer to as the 'irony of rigor:' the contradictory double-movement through which students of color with disabilities desired inclusion into 'rigorous' charter schools which then excluded them using 'rigor' as a central feature of student pushout practices. We present the irony of rigor in three interrelated acts: Act I: the lure of rigor (i.e. what drew parents to charter schools); Act II: the body meets rigor (i.e. how schools disciplined and managed student differences); and Act III: the consequences of rigor (i.e., what happened to students and parents while and after experiencing rigorous practices). We contextualize the irony of rigor within the relationship between disability, race, and neoliberalism.